2021
DOI: 10.1038/s41598-021-81761-z
|View full text |Cite
|
Sign up to set email alerts
|

Response differences of HepG2 and Primary Mouse Hepatocytes to morphological changes in electrospun PCL scaffolds

Abstract: Liver disease cases are rapidly expanding across the globe and the only effective cure for end-stage disease is a transplant. Transplant procedures are costly and current supply of donor livers does not satisfy demand. Potential drug treatments and regenerative therapies that are being developed to tackle these pressing issues require effective in-vitro culture platforms. Electrospun scaffolds provide bio-mimetic structures upon which cells are cultured to regulate function in-vitro. This study aims to shed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The surface topography of the CS/PEO scaffolds discussed above plays an essential role in the behavior of tumor cells and the spontaneous formation of the breast cancer microtissues that resemble in vivo cancer tissues. The dimensions and morphology of CS/PEO nanofibrous scaffolds resemble the nano- and sub-micron scale of ECM structures in the in vivo tumor microenvironment . The characteristics and surface topography of these scaffolds induce spheroid formation and the development of microtissues by mechanisms which are currently not completely understood but we suppose the following possibilities as potential mechanisms for the formation: (i) cell–cell interactions result in tight cell aggregates which form the spheroid through self-assembly and then the formed spheroids are held together forming the 3D microtissues and (ii) outward proliferation of a fiber-attached cell to form a spheroid which enlarges in size and proliferates more and more forming the 3D microtissues.…”
Section: Resultsmentioning
confidence: 96%
“…The surface topography of the CS/PEO scaffolds discussed above plays an essential role in the behavior of tumor cells and the spontaneous formation of the breast cancer microtissues that resemble in vivo cancer tissues. The dimensions and morphology of CS/PEO nanofibrous scaffolds resemble the nano- and sub-micron scale of ECM structures in the in vivo tumor microenvironment . The characteristics and surface topography of these scaffolds induce spheroid formation and the development of microtissues by mechanisms which are currently not completely understood but we suppose the following possibilities as potential mechanisms for the formation: (i) cell–cell interactions result in tight cell aggregates which form the spheroid through self-assembly and then the formed spheroids are held together forming the 3D microtissues and (ii) outward proliferation of a fiber-attached cell to form a spheroid which enlarges in size and proliferates more and more forming the 3D microtissues.…”
Section: Resultsmentioning
confidence: 96%
“…One of the endeavours in this field is creating a three-dimensional foundation that can provide a suitable niche for cells to behave as they would in vivo. For this purpose, electrospinning of polymers has been widely used to produce fibrous scaffolds as it enables easy manipulation of chemical structure and fibre architecture [6][7][8]. Nevertheless, scaffolds from synthetic polymers lack natural biomolecular signals which cells benefit from to modulate their functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on similar electrospun fibres have shown that different cell types can respond in a comparable manner, and co-culture can initiate other functions. 37,56,86,87 As the liver is a complex organ, a layer of liver tissue is usually composed of hepatocytes, epithelial cells, Kupffer cells, stellate cells, and liver sinusoidal endothelial cells. How to design or to use a potential scaffold depends on what function is required.…”
Section: Discussionmentioning
confidence: 99%
“…DNA content per cell is absolute, therefore indicating the cell number per scaffold so that we can understand the cell attachment and proliferation. 39,56 All groups showed an upward trend on day 7 compared to 24 hours, while the SSD and NSD groups showed a slight decrease on day 14. Moreover the SSD group shows the highest DNA content on days 7 and 14.…”
Section: Cell Viability and Dna Quantificationmentioning
confidence: 93%